Impact behaviour of glass fibre-reinforced epoxy/aluminium fibre metal laminate manufactured by Vacuum Assisted Resin Transfer Moulding. (15th April 2016) - Ortiz de Mendibil, I.; Aretxabaleta, L.; Sarrionandia, M.; Mateos, M.; Aurrekoetxea, J.
Abstract: Fibre Metal Laminates have been manufactured by liquid moulding. Flow paths have been drilled to enable the impregnation through the aluminium sheets. The effect of these holes on the low velocity impact behaviour has been studied. Damage mechanisms, dissipated energy and peak force of drilled samples have been compared to those of reference samples without holes. Results show that the presence of the holes has no effect on the performance of the plate and that the internal damage is confined to the surrounding of the impact zone. When the holes are inside the impact contact zone cracks in aluminium sheets propagate through the holes, but their effect is mitigated by the fibre bridging mechanism. Holes located out of the impact contact zone have no effect in the damage mechanisms.